2019
DOI: 10.1002/qj.3618
|View full text |Cite
|
Sign up to set email alerts
|

The impact of horizontal atmospheric resolution in modelling air–sea heat fluxes

Abstract: Climate modes as simulated by global climate models are often found to be considerably weaker than are observed. One possibility is that coarse‐resolution climate models do not capture turbulent air–sea fluxes sufficiently. Ensemble experiments with the same atmospheric configuration of the Met Office Hadley Centre climate model, forced with observed sea‐surface temperatures (SST) and at three different horizontal model resolutions (approximately 130, 60 and 25 km), are used to test the sensitivity of air–sea … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 49 publications
3
7
0
Order By: Relevance
“…Both the stronger near-surface wind and less near-surface specific humidity contribute to higher ventilation efficiencies and enhanced ocean forcing of the atmosphere along the Kuroshio, resulting in more turbulent latent heat flux in the HRMs. This agrees with Wu et al (2019). For…”
Section: Summary and Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Both the stronger near-surface wind and less near-surface specific humidity contribute to higher ventilation efficiencies and enhanced ocean forcing of the atmosphere along the Kuroshio, resulting in more turbulent latent heat flux in the HRMs. This agrees with Wu et al (2019). For…”
Section: Summary and Discussionsupporting
confidence: 89%
“…In an earlier study (Wu et al, 2019), we have found that latent heat fluxes in tropics are suppressed in higher-resolution AGCMs, especially in the western Pacific. The local decreased latent heat can strengthen the WNPSH.…”
Section: Accepted Articlementioning
confidence: 69%
See 1 more Smart Citation
“…The response of WVP to warming is strongly constrained by Clausius-Clapeyron, but changes in U 10m are a function of changes in extratropical circulation and are less well constrained in GCMs. It is possible more advanced and higher-resolution models will project a different response in cyclone wind speed (Baker et al 2019;Davini et al 2017;Gonzalez et al 2019;Jiaxiang et al 2020;Roberts et al 2020;Wu et al 2019). However, across the GCMs evaluated here moisture changes dominate the change in WCB moisture flux.…”
Section: Regression Analysismentioning
confidence: 94%
“…Another difference that cannot be neglected is the horizontal resolution, which is much higher in HAP-PI-CAM5 (∼25 km) than the coupled runs (∼100 km; Table 1). There is growing evidence of added value of high resolution modeling in simulating the global hydrological cycle as well as precipitation extremes (Prein et al, 2016;Roberts et al, 2018;Van Der Wiel et al, 2016;Vannière et al, 2018;Wu et al, 2019). For extreme precipitation, specifically, heavier extreme precipitation is permitted overall across the globe in higher-resolution simulations (Chen & Dai, 2019;O'Brien et al, 2016;Wehner et al, 2014).…”
Section: Spatial Resolutionmentioning
confidence: 99%